(untitled) (Applied Biological Research, 2023)
The present study was aimed to examine the therapeutic values of pulp and peel extracts of Hylocereus undatus by comparing the chemical compounds identified by using GC-MS. Antioxidant activities were measured using DPPH●, ABTS●+, superoxide radical, FRAP and phosphomolybdenum reduction assay. Antidiabetic and anti-inflammatory activities were determined using α-amylase inhibition method and heat induced hemolytic technique. The results showed that both the extracts reduced the oxidative stress with pulp extract showing stronger antioxidant activity. The antidiabetic and anti-inflammatory activities of pulp extract were greater than peel extract with IC50 values of 222.97 and 16.56 µg mL-1, respectively. GC-MS analysis showed the presence of phytosterols, steroids, triterpene, phenolic compounds and esters of fatty acids. The study shows the presence of bioactive compounds in H. undatus pulp and peel extracts with promising health benefits.